2016
DOI: 10.1016/j.lithos.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of natural diamond shocked to 60 GPa; implications for Earth and planetary systems

Abstract: The possible presence of the high-density carbon polymorph with hexagonal symmetry known as "lonsdaleite" provides an important marker for shock impact events. It is typically considered to form as a metastable phase produced from graphite or other carbonaceous precursors. However, its existence has recently been called into question. Here we collected high-resolution synchrotron X-ray diffraction data for laboratory-shocked and natural impact diamonds that both show evidence for deviations from cubic symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 47 publications
1
34
0
4
Order By: Relevance
“…The previous experimental and computational results demonstrated that the cubic diamond could transform into lonsdaleite phase under non-hydrostatic loading conditions. 18,[56][57][58] In fact, phase transition was rstly considered by Ruoff et al as a possible failure mode for a diamond at, which was pressed by a spherical diamond indenter. 59 Later on, by coupling the indentation loading with micro-Raman spectroscopy, Gogotsi et al directly observed the phase transitions of diamond during indenting process, including the transition of cubic diamond to lonsdaleite (hexagonal diamond) and amorphous diamond phase.…”
Section: Probable Physical Processes Underneath the Indentermentioning
confidence: 99%
“…The previous experimental and computational results demonstrated that the cubic diamond could transform into lonsdaleite phase under non-hydrostatic loading conditions. 18,[56][57][58] In fact, phase transition was rstly considered by Ruoff et al as a possible failure mode for a diamond at, which was pressed by a spherical diamond indenter. 59 Later on, by coupling the indentation loading with micro-Raman spectroscopy, Gogotsi et al directly observed the phase transitions of diamond during indenting process, including the transition of cubic diamond to lonsdaleite (hexagonal diamond) and amorphous diamond phase.…”
Section: Probable Physical Processes Underneath the Indentermentioning
confidence: 99%
“…Carbon in the Earth may exist in various forms including carbides, diamond, graphite, lonsdaleite, hydrocarbons, CO 2 , and carbonates depending on the oxygen fugacity and P-T conditions (Dasgupta and Hirschmann, 2010;Hazen et al, 2013;Jones et al, 2016). Although it is generally thought that the conditions of the Earth's deep interior and of the subducting slab materials may be not compatible with the stability of carbonates or carbonate-rich liquid (Anzolini et al, 2016;Thomson et al, 2016), the observation of carbonate inclusions in diamonds potentially brought up to the Earth's surface from the deep mantle indicates that carbonates can exist at least locally in the mantle (e.g., Stachel et al, 1998Stachel et al, , 2000Leost et al, 2003;Bulanova et al, 2010).…”
Section: Implications For the Deep Carbon Cyclementioning
confidence: 99%
“…However, only controversial findings of lonsdaleite have been reported in eclogites from the Kola Peninsula [14], glaucophane-bearing eclogites of the Maksyutov complex [15], and garnet-biotite gneiss from the Kokchetav massif [16]. In contrast to lonsdaleite, which is always found as aggregates with other carbon polymorphs [17], diamond and graphite commonly occur separately, although in some localities, these carbon polymorphs can be recognized in an intimate association, as well (see [18] and the references therein). According to [19], most diamonds nucleated heterogeneously on mineral seeds (e.g., sulphide, native iron, wustite, monocrystalline graphite), which could lower the energy barrier to nucleation of monocrystals.…”
Section: Introductionmentioning
confidence: 99%